Access to Primary Care Physicians and Mortality in Washington State: Application of a 2‐Step Floating Catchment Area. Issue 3 (15th December 2019) - Amiri, Solmaz; Espenschied, Jonathan R.; Roll, John M.; Amram, Ofer
Abstract: Objective: To measure access to primary care physicians (PCPs) using a 2‐step floating catchment area and explore the associations between access to PCPs and mortality related to all‐causes, cancers, and heart disease in Washington State. Methods: An ecological study employing generalized linear regression models of access to PCPs and mortality rates in 4, 761 block groups in Washington State in 2015. To measure access to PCPs, we used a 2‐step floating catchment area approach, taking into account area‐level population, supply of PCPs, and travel time between PCPs, as well as area‐level population with a distance decay function. Results: A 1‐unit increase in PCP access score was associated with a reduction of 4.2 all‐cause deaths per 100, 000 people controlling for socioeconomic characteristics. A 1‐unit increase in PCP access score was associated with a reduction of 2.7 cancer deaths and a reduction of 2.1 heart disease deaths per 100, 000 people controlling for socioeconomic characteristics. Conclusions: Better access to PCPs was associated with lower mortality from all‐causes, cancers, and heart disease. The 2‐step floating catchment area approach can help with the identification of PCP shortage areas, the development of rural residency programs, and the expansion of the physician workforce in Washington State and other regions.